Synthesis of MnO2 as Supercapacitor Electrodes Material by Green Chemistry Method Through Dehydroxylation of Tangerine Peel (Citrus reticulata) Essential Oil - Izzah, Dewi Jalinan; Fajaroh, Fauziatul; Aliyatulmuna, Adilah; Sumari, Sumari; Marfu'ah, Sitti (Al-Kimia, 2022)
In this era, most technology requires electronic equipment. The performance of electronic equipment may be affected by energy storage components like a supercapacitor, so the development of supercapacitor electrode materials using green chemical methods needs to be pursued. Material with a good specific capacitance is MnO2. Most of the MnO2 synthesis methods are not based on green chemistry, so there is an alternative method. One of them is by utilizing the waste from tangerine peels. This study aimed to synthesize MnO2 through dehydroxylation of tangerine peel essential oil. The steps for conducting this research consisted of isolation of tangerine peel essential oil, analysis of the constituent components of tangerine peel essential oil, synthesis of MnO2 through dehydroxylation of essential oils tangerine peel, and MnO2 characterization. XRD results showed that MnO2 synthesized at pH 11 had the highest percentage of α-MnO2 (97%). This is evidenced by the presence of α-MnO2 diffractogram according to the ICSD No.20227. The SEM results showed that MnO2 had a spherical morphology with a particle diameter of 39.51 nm. α-MnO2 has a larger tunnel structure compared to β- and γ-MnO2, making the charge-discharge process easier so that α-MnO2 has the potential as a supercapacitor electrode material.